The The Influence of Digital Payment Usage and Understanding of Islamic Financial Literacy on Consumer Behavior With Self-Control as A Moderating Variable: - - Nurlatifah Umi Oktafiani; Efi Syarifudin; Sulaeman Jajuli (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
The presence of increasingly widespread internet networks and rapid technological developments have brought changes to people's consumption patterns. This development opens up opportunities for innovation in digital financial technology, such as digital payments. Digital payment is a payment system that offers a variety of conveniences to society, especially for the millennial generation and generation Z, where this generation grew up amidst the development of information technology. It is now hoped that the ease of obtaining adult information will make it easier for the younger generation to access and understand sharia financial literacy and to have high self-control so that they are able to respond wisely to the convenience offered by digital payments. This research aims to obtain empirical facts regarding the influence of digital payments and sharia financial literacy on the consumer behavior of the millennial generation and generation Z in Banten province with self-control as a moderating variable. This research is quantitative research with purposive sampling as the sampling method. Data was obtained by distributing questionnaires in Google form to 118 respondents. The data analysis method used is Multiple Linear Regression and Moderated Regression Analysis (MRA) with SPSS IBM Statistics 25 software. The results of this research show that the Digital Payment variable has a positive effect on the Consumptive Behavior variable. Meanwhile, the Sharia Financial Literacy variable has no significant effect on the Consumer Behavior Variable. Self-Control does not moderate the influence of Digital Payment on consumptive behavior and Self-Control also does not moderate the influence of Sharia Financial Literacy on consumptive behavior. The contribution of the influence of the Digital Payment and Sharia Financial Literacy variables to the Consumptive Behavior variable after the moderating variable (Self Control) is 14.5%, the remaining 85.5% is influenced by other variables not examined in this research. Keywords: digital payment, sharia financial literacy, consumer behavior, self-control, generation Z